2021
DOI: 10.1371/journal.pone.0247660
|View full text |Cite
|
Sign up to set email alerts
|

Control strategies for COVID-19 epidemic with vaccination, shield immunity and quarantine: A metric temporal logic approach

Abstract: Ever since the outbreak of the COVID-19 epidemic, various public health control strategies have been proposed and tested against the coronavirus SARS-CoV-2. We study three specific COVID-19 epidemic control models: the susceptible, exposed, infectious, recovered (SEIR) model with vaccination control; the SEIR model with shield immunity control; and the susceptible, un-quarantined infected, quarantined infected, confirmed infected (SUQC) model with quarantine control. We express the control requirement in metri… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
54
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(55 citation statements)
references
References 47 publications
1
54
0
Order By: Relevance
“…In the early stages of the pandemic in the UK, Crellen et al (2021) used an SEIR model to investigate the e↵ect of di↵erent mean durations of immunity (90-365 days), on short-term dynamics and long-term endemic behaviour, in an age-based model, in the absence of vaccination, under various assumptions about the time-varying e↵ective reproduction number. In Xu, Wu, and Topcu (2021), the authors consider a short-term SEIR model over 200 days, that optimises vaccination roll-out, subject to thresholds on death rates, cumulative deaths, and target numbers of those vaccinated. It assumes 100% vaccine e cacy, with no waning of immunity following vaccination or infection.…”
Section: Background and Literature On Vaccine Modelsmentioning
confidence: 99%
See 1 more Smart Citation
“…In the early stages of the pandemic in the UK, Crellen et al (2021) used an SEIR model to investigate the e↵ect of di↵erent mean durations of immunity (90-365 days), on short-term dynamics and long-term endemic behaviour, in an age-based model, in the absence of vaccination, under various assumptions about the time-varying e↵ective reproduction number. In Xu, Wu, and Topcu (2021), the authors consider a short-term SEIR model over 200 days, that optimises vaccination roll-out, subject to thresholds on death rates, cumulative deaths, and target numbers of those vaccinated. It assumes 100% vaccine e cacy, with no waning of immunity following vaccination or infection.…”
Section: Background and Literature On Vaccine Modelsmentioning
confidence: 99%
“…Models developed by Xu, Wu, and Topcu (2021), Ghostine et al (2021), Wintachai andPrathom (2021), andAntonini, Calandrini, andBianconi (2021) are age-homogeneous. In the early stages of the pandemic in the UK, Crellen et al (2021) used an SEIR model to investigate the e↵ect of di↵erent mean durations of immunity (90-365 days), on short-term dynamics and long-term endemic behaviour, in an age-based model, in the absence of vaccination, under various assumptions about the time-varying e↵ective reproduction number.…”
Section: Background and Literature On Vaccine Modelsmentioning
confidence: 99%
“…These vaccines have shown promising effects and mass vaccination programmes are underway worldwide. While such programmes are promising, several modelling studies have shown that as vaccination is rolled out, proper vaccine allocation is necessary [5,6,7,8,9] and maintenance of NPIs is still required to prevent the increase of hospitalisations and deaths, particularly before completing full vaccination [10,11,12,13,14]. In Portugal, vaccination has been rolled out in two main phases: the first focused in healthcare professionals and vulnerable individuals (residents in nursing homes, individuals at higher risk of severe disease due to preexisting medical conditions and those aged ≥ 80 years old), and the second one for the general population, organised by age groups, from 79 years old downwards.…”
Section: Introductionmentioning
confidence: 99%
“…[ 16 ] or Xu et al . [ 17 ], vaccination is modelled in a new compartment of SIR-type by considering that susceptible individuals are vaccinated without delay.…”
Section: Introductionmentioning
confidence: 99%
“…Concerning pharmaceutical interventions, most of the models deal with the vaccination. In Dashtbali & Mirzaie [14], Giordano et al [15], Moore et al [16] or Xu et al [17], vaccination is modelled in a new compartment of SIR-type by considering that susceptible individuals are vaccinated without delay.…”
Section: Introductionmentioning
confidence: 99%